2011
DOI: 10.1016/j.theriogenology.2010.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Sex-sorted bovine spermatozoa and DNA damage: II. Dynamic features

Abstract: This study examined the dynamic response of Spermatozoa DNA Fragmentation after sex selection in bulls using a MoFlo(®) SX (Beckman Coulter, Miami FL) spermatozoa sorter. The dynamic response of spermatozoa DNA fragmentation refers to the changing values of SDF, i.e., rate of SDF (rSDF), when analyzed periodically over a set incubation time at 37 °C. A dynamic assessment of SDF using non-sorted and sex-sorted spermatozoa samples during 72 h of incubation at 37 °C was performed. Results showed a reduced DNA lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 29 publications
1
24
0
2
Order By: Relevance
“…In fact, this is what we have observed in bovine where, as in deer, the baseline SDF is greater in FT-Conv than in FT-Sex-Sort samples, but the rate of SDF is greater in FT-Sex-Sort samples than in FT-Conv samples. This is an interesting effect because when both curves are plotted together, a crossover in the tendency of SDF (termed the crossover positioning time; Gosálvez et al, 2011b) for both conventional and sex-sorted samples is produced (Figure 4a). This aforementioned crossover positioning time was not produced in the deer sperm Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this is what we have observed in bovine where, as in deer, the baseline SDF is greater in FT-Conv than in FT-Sex-Sort samples, but the rate of SDF is greater in FT-Sex-Sort samples than in FT-Conv samples. This is an interesting effect because when both curves are plotted together, a crossover in the tendency of SDF (termed the crossover positioning time; Gosálvez et al, 2011b) for both conventional and sex-sorted samples is produced (Figure 4a). This aforementioned crossover positioning time was not produced in the deer sperm Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the dynamic behavior of conventional (unfilled circles) and sex-sorted sperm samples (filled circles) in a) bulls, modified fromGosálvez et al (2011b), and b) white-tailed deer. CPT = crossover positioning time.…”
mentioning
confidence: 99%
“…The high-speed flow cytometry sorting process could reduce sperm lifespan (e.g. in terms of DNA fragmentation rates, as observed by Gosálvez et al 2011) and increase ROS content during long fertilisation times (Johnson et al 1999;Garner 2006). The initial hypothesis was that M199 medium could have an advantage over the other two media in terms of minimising osmotic stress to MII oocytes as result of passage from IVM to IVF, protecting oocytes and sperm against oxidative stress through antioxidants and preventing oocyte aging.…”
Section: Discussionmentioning
confidence: 99%
“…flow cytometry) that SS have undergone. The high speed during the sorting process could reduce sperm lifespan (Gosálvez et al 2011) and increase ROS content during long fertilisation periods (Garner et al 2013;Rath et al 2013). A decrease in sperm chromatin stability could easily be associated with mechanical injury, enhanced via DNA exposure to Hoechst 33342 and/or laser illumination (Garner 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in the dose rate from 10 × 10 6 to 2.1 × 10 6 sperm caused an 8.3% decrease in conception rate in frozen CON semen, but a 13.6% decrease for frozen SS semen (DeJarnette et al, 2011). In addition, it has been shown that the increases over time in sperm DNA fragmentation in frozen-thawed semen samples was faster for SS semen than CON semen (Gosálvez et al, 2011b). Implementation of liquid SS semen is not without its own challenges.…”
Section: Discussionmentioning
confidence: 99%